Peran Dan Kerjasama Orang Tua Dalam Pendidikan Anak - Faridhatul Anawaty, Mardiyana (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2022)
Early childhood education is provided from birth to 6 years of age. Children's education is not only the responsibility of the school but also the responsibility of parents. Parents are the child's first environment as well as the child's primary educator. Parents play a role in providing proper guidance and direction so that children's growth and development can be optimal. For this reason, the participation of both parents is very large in the development of children. This article will discuss the role and collaboration of parents in children's education. The method used in this research is descriptive method with literature study. The family environment, especially parents, is the first environment for children where children grow and develop. Therefore, it is important for parents to understand the development of their children. Children have their own potential. This potential can develop if parents can provide the right stimulation to children. efforts that parents can make to explore children's potential are (1) recognize children's potential, (2) provide proper stimulation, (3) provide support, (4) give praise, (5) invite children to be creative according to their imagination, (6) direct the child, and (7) encourage the child to learn. Father and mother complement each other to provide stimulation in child development